The Pengaruh Beban Kerja Mental dan Kualitas Tidur terhadap Kelelahan Kerja Pengemudi - Wahyuni, Tsania; Gunawan, Suwardi; Utomo, Dutho Suh (Jurnal Ilmiah Wahana Pendidikan, 2024)
PT Bustani Bersaudara is an LPG gas distribution agent company. Gas distribution activities are carried out by a driver who delivers gas to the delivery destination. However, after conducting interviews with drivers, some drivers felt some problems such as feeling a little tired from driving for a long period of time, and the type of work that is monotonous and requires high concentration during work makes drivers feel mental workload. Based on these problems, will calculate the mental workload, work fatigue, and sleep quality of drivers and analyze the influence between mental workload and sleep quality on work fatigue in drivers. The methods used in this study include NASA-TLX to measure mental workload, PSQI (Pittsburgh Sleep Quality Index) method to measure sleep quality level, and IFRC (Industrial Fatigue Research Committee) method to measure work fatigue level. The measurement results of the NASA-TLX method obtained an average mental load of 74.956 which is classified as a moderate mental workload category. The PSQI method obtained the average result of sleep quality level of 9.9 which is classified as a low sleep quality category. The IFRC method obtained the average result of work fatigue level of 57.4 which is classified as mild work fatigue category. The effect of mental workload on work fatigue obtained a significance value of 0.251, which means that mental workload has no effect on work fatigue because the significance value is > 0.05. The effect of sleep quality on work fatigue obtained a significance value of 0.345, which means that sleep quality has no effect on work fatigue because the significance value is > 0.05. Simultaneously, the effect of mental workload and sleep quality on work fatigue produces a significance value of 0.145, which means they simultaneously have no influence.